2018
DOI: 10.12659/msm.904378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhalation Anesthesia vs. Total Intravenous Anesthesia (TIVA) vs. Spinal-Epidural Anesthesia on Deep Vein Thrombosis After Total Knee Arthroplasty

Abstract: BackgroundThe objective of the present study was to evaluate the varying efficacy of general anesthesia (GA), combined spinal-epidural anesthesia (CSEA), and total intravenous anesthesia (TIVA) on the occurrence of deep vein thrombosis (DVT) following total knee arthroplasty (TKA).Material/MethodsFrom July 2013 to May 2015, a total of 197 cases of patients who had undergone TKA treatment at either the Drum Tower Hospital or Nanjing General Hospital of Nanjing Military Command were recruited to participate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, since the admission records did not distinguish the type of diabetes, the influence of the type on DVT needs to be further studied. Third, different anesthetic methods exert different influences on hemodynamics, thus affecting the occurrence of postoperative DVT [ 30 ]. In our study, all patients received general or intraspinal anesthesia, and no significant difference was observed between them ( p = 0.716).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the admission records did not distinguish the type of diabetes, the influence of the type on DVT needs to be further studied. Third, different anesthetic methods exert different influences on hemodynamics, thus affecting the occurrence of postoperative DVT [ 30 ]. In our study, all patients received general or intraspinal anesthesia, and no significant difference was observed between them ( p = 0.716).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found a statistically lower incidence of DVT in RG compared with CG (9.46% vs. 24.00%), suggesting that EA can reduce the risk of DVT in TKA patients, which is similar to the findings of Hafezi et al [ 17 ]. EA may reduce the risk of DVT development by preventing postoperative hypercoagulability, thus reducing postoperative thromboembolic complications [ 28 ]. Other studies have shown that under EA, anaesthetics are absorbed into the blood through the epidural space, which can inhibit the aggregation, release, and adhesion of platelets and improve the coagulation function of patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we do not distinguish between the types of diabetes, and different types of diabetes may have different effects on DVT. Third, different anesthetic methods exert different influence on hemodynamics, thus affecting the occurrence of postoperative DVT [31]. In this study, all patients received general or intraspinal anesthesia, and no significant difference was observed between them (p=0.940).…”
Section: Discussionmentioning
confidence: 64%